Critical approach to methods of glacier reconstruction in high Asia and discussion of the probability of a Qinghai-Xizang(Tibetan) Inland ice - Kuhle, Matthias (2007)
This overview discusses old and new results as to the controversy on the past glacier extension in High Asia, which has been debated for 35 years now. This paper makes an attempt to come closer to a solution. H.v. Wissmann's interpretation (1959) of a small-scale glaciation contrasts with M. Kuhle's reconstruction (1974) of a large-scale glaciation with a 2.4 million km(2) extended Qinghai-Xizang (Tibetan) inland glaciation and a Himalaya-Karakorum icestream network. Both opinions find support but also contradiction in the International and Chinese literature (Academia Sinica). The solution of this question is of supraregional importance because of the subtropical position of the concerned areas. In case of large albedo-intensive ice surfaces, a global cooling would be the energetical consequence and, furthermore, a breakdown of the summer monsoon. The current and interglacial heat-low above the very effective heating panel of the Qinghai-Xizang (Tibetan) Plateau exceeding 4000 m, which gives rise to this monsoon circulation, would be replaced by the cold-high of an inland ice. In addition, the plate-tectonically created Pleistocene history of the uplift of High Asia - should the occasion arise up to beyond the snowline (ELA) - would attain a paleoclimatically great, perhaps global importance. In case of a heavy superimposed ice load, the question would come up as to the glacio-isostatic interruption of this primary uplift. The production of the loesses sedimentated in NE-China and their very probable glacial genesis as well as an eustatic lowering of the sea-level by 5 to 7 m in the maximum case of glaciation are immediately tied up with the question of glaciation we want to discuss. Not the least, the problems of biotopes of the sanctuary-centres of flora and fauna, i.e., interglacial re-settlement, are also dependent on it. On the basis of this Quaternary-geomorphological-glaciological connection, future contributions are requested on the past glaciation, the current and glacial permafrost table and ...